Effect of Saccharum spontaneum Linn. on Lysosomal enzymes of Uro-lithiatic rats - M. Sathya and R. Kokilavani (Journal of Applied Pharmaceutical Science)
The ethanolic root extract of Saccharum spontaneum of family Poaceae was used to treatthe urolithiasis induced by glycolic acid On this course, the extract also repairs the changesthat happened in the lysosomal enzymes like β-D-glucuronidase, xanthine oxidase in liver and kidney and n-acetyl -d-glucosaminidase in serum, liver, kidney and urine of the urolithiatic rats. The ethanolic root extract (200 and 300 / kg b.w.) elevated the levels of reduced β-D-glucuronidasein liver and n-acetyl -d-glucosaminidase in liver and kidney and reduced the level of xanthineoxidase in liver and kidney and n-acetyl -d-glucosaminidase in serum and urine significantly (p
Keywords: Saccharum spontaneum,Lysosomal Enzymes,Thiazide,Glycolic acid